Blepharoplasty Complications - Mack, William P. (Facial Plastic Surgery, 2012)
There are three major areas of concern for a patient who has complications following a cosmetic blepharoplasty: cosmetic issues, functional issues, and uncomfortable/symptomatic issues or a combination of the above. An emphasis will be placed on avoiding cosmetic eyelid complications as well as the medical and surgical management of complications.
Keywords: blepharoplasty; lid retraction; orbital hemorrhage; dry eye syndrome; ptosis